Development of a bicistronic expression system in the branchiopod crustacean Daphnia magna. Issue 12 (14th November 2017) - Kumagai, Hitoshi; Matsuura, Tomoaki; Kato, Yasuhiko; Watanabe, Hajime
Summary: The viral 2A peptides have recently been used for bicistronic expression in various organisms. In this system, a single mRNA that codes for two proteins flanking the 2A peptide can be translated simultaneously into each protein by ribosomal skipping at this peptide sequence. Here, we tested the function of the Thosea asigna insect virus 2A (T2A) peptide in the branchiopod crustacean Daphnia magna —an emerging model of evolutionary developmental biology. First, we used transgenic Daphnia that expresses a potential bicistronic RNA containing mCherry and histone H2B‐ green fluorescent protein (GFP) open reading frames upstream and downstream of the T2A sequence, respectively. Microscopic observation revealed difference of localization of the two proteins in the cell, homogenous distribution of mCherry and nuclear localization of H2B‐GFP. Second, we changed localization of mCherry from cytoplasm to plasma membrane by attachment of a consensus myristoylation motif in the bicistronic reporter. RNA that codes for this new bicistronic reporter was injected into eggs. At gastrulation stage, we found spectrally distinct fluorescence with enough intensity and resolution to detect membrane localized mCherry and nuclear GFP. These results indicate that the T2A peptide functions in D. magna and T2A‐mediated bicistronic expression would be a promising tool for evo‐devo studies of this species.